A COMPARATIVE KEYWORDS ANALYSIS IN PET CAFÉ AND REGULAR CAFÉ REVIEWS: A CORPUS STUDY - Hariyatmi, Sri (LLT Journal: A Journal on Language and Language Teaching, 2022)
This paper aims to investigate the most frequently used keywords in pet’s café and regular cafe to identify the linguistics discrepancies between the reviews in the two cafes. A self- created corpora of pet’s café and regular café’s reviews were collected from TripAdvisor and google map and used as the main data to compare the linguistic features in each corpus. The analysis was conducted by using AntConc 3.5.9 for Windows (64-bit) to compare the keywords and concordance lines of notable keywords. A comparison of the keyword analysis indicates that the big discrepancies between the two corpora is the use of second- and third-persons pronouns  in pet café review and the use of the first-person pronouns in regular café review. This pronouns choice suggests that in pet café, the writers adopt customers and product- based review, whereas in regular café, the writer tend to focus their reviews on author-based review. Another notable finding is the absence of Wi-fi in pet café review and the absence of adverb and preposition in regular café. Despite the difference, the reviews in both cafés are heavily dominated by the use of verbs, nouns, and only small number of adjectives found in each corpus.